GC–MS analysis of 4-hydroxyproline: elevated proline hydroxylation in metformin-associated lactic acidosis and metformin-treated Becker muscular dystrophy patients - Svetlana Baskal; Rene A. Posma; Alexander Bollenbach; Willem Dieperink; Stephan J. L. Bakker; Maarten W. Nijsten; Daan J. Touw; Dimitrios Tsikas (Amino Acids)
Abstract Metformin (N,N-dimethylbiguanide), an inhibitor of gluconeogenesis and insulin sensitizer, is widely used for the treatment of type 2 diabetes. In some patients with renal insufficiency, metformin can accumulate and cause lactic acidosis, known as metformin-associated lactic acidosis (MALA, defined as lactate ≥ 5 mM, pH < 7.35, and metformin concentration > 38.7 µM). Here, we report on the post-translational modification (PTM) of proline (Pro) to 4-hydroxyproline (OH-Pro) in metformin-associated lactic acidosis and in metformin-treated patients with Becker muscular dystrophy (BMD). Pro and OH-Pro were measured simultaneously by gas chromatography–mass spectrometry before, during, and after renal replacement therapy in a patient admitted to the intensive care unit (ICU) because of MALA. At admission to the ICU, plasma metformin concentration was 175 µM, with a corresponding lactate concentration of 20 mM and a blood pH of 7.1. Throughout ICU admission, the Pro concentration was lower compared to healthy controls. Renal excretion of OH-Pro was initially high and decreased over time. Moreover, during the first 12 h of ICU admission, OH-Pro seems to be renally secreted while thereafter, it was reabsorbed. Our results suggest that MALA is associated with hyper-hydroxyprolinuria due to elevated PTM of Pro to OH-Pro by prolyl-hydroxylase and/or inhibition of OH-Pro metabolism in the kidneys. In BMD patients, metformin, at the therapeutic dose of 3 × 500 mg per day for 6 weeks, increased the urinary excretion of OH-Pro suggesting elevation of Pro hydroxylation to OH-Pro. Our study suggests that metformin induces specifically the expression/activity of prolyl-hydroxylase in metformin intoxication and BMD.